Reducing Pain on A Severe Scale After Caesarean Section Surgery With LI 4 and HT 7 Acupressure - Hanum, Sri Mukhodim Faridah; Firdausi, Zahro (Universitas Muhammadiyah Sidoarjo, 2024)
Pain after caesarean section surgery is a physiological symptom that is usually experienced by postpartum mothers. This pain can be treated in various ways, including acupressure. The combination of giving acupressure at points LI 4 and HT 7 can reduce the pain scale of post-operative and post-operative mothers. Objective: To determine the effect of LI 4 and HT 7 acupressure on reducing the pain scale after SC. Method: This research is a quasi-experimental research with a one-group pretest and posttest design. The sample for this research is 23 postpartum mothers with a consecutive sampling technique. The data collection technique uses a list of questions or a questionnaire with NRS. The accumulated data will be analyzed using the paired T-test. The results of the paired T-testshowed a p-value = 0.000, meaning that there was a significant difference in the reduction in pain scale before and after the intervention. There is an effect of giving acupressure points LI 4 and HT 7 on reducing the pain scale after SectioCesarea surgery.